A randomized trial of the effect of vaccine injection speed on acute pain in infants. Issue 39 (7th September 2016) - Taddio, Anna; Wong, Horace; Welkovics, Ben; Ilersich, Angelo L.; Cole, Mara; Goldbach, Morton; Ipp, Moshe
Highlights: We evaluated the effect of fast vs. slow injections on pain during routine vaccinations in infants. Fast injections caused less pain during the first vaccine injection but not the second vaccine injection. Fast injections are recommended because of the potential for less pain. Abstract: Objective: This study compared the pain caused from fast vs. slow vaccine injections. Methods: Infants aged 2–6 months receiving primary immunizations were randomized to fast (2–4 mL/s) or slow (5–10 mL/s) injections during routine 0.5 mL Diphtheria, Tetanus, acellular Pertussis, Inactivated Polio Virus, Haemophilus influenzae type b vaccine (DTaP-IPV-Hib) injections. Those aged 2 and 4 months additionally received 0.5 mL Pneumococcal Conjugate Vaccine (PCV) injections. A research assistant and parent unaware of treatment allocation and hypothesis assessed pain using validated and recommended tools, including; the Modified Behavioural Pain Scale (MBPS, range 0–10), cry duration, and Numerical Rating Scale (NRS, range 0–10). The primary outcome was infant pain score using the MBPS. Results: Altogether, 120 were recruited; 61 were randomized to fast injections and 59 to slow injections. One hundred and ninteen infants participated. There were no differences in characteristics, including; age (p = 0.994) and sex (p = 0.540). The mean MPBS score (standard deviation) during DTaP-IPV-Hib injection was lower in the fast injection group: 6.4 (2.7) vs. 7.4 (2.5), respectively; p = 0.046. Regression analysis demonstrated a positive correlation between injection speed and pain. There were no other differences between groups. Conclusion: Fast injection reduced injection-induced pain in infants receiving DTaP-IPV-Hib but not PCV vaccine. Fast injections are recommended when administering vaccines because of the potential for a reduction in pain, feasibility and practicality. Trial registration:NCT02504398